(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current study aims to identify the level of adaptation of the curriculum for visually handicapped pupils from the point of view of their teachers as well as to identify the level of adaptation of the educational programs offered to visually handicapped pupils from the point of view of their teachers. In order to achieve the goals of the research, the researcher developed two tools to measure the adaptation of curricula and educational programs for pupils with visual handicapped from the point of view of teachers. The sample included (60) teachers from Al Noor Institute for Blinders in Baghdad, the two tools were applied to them, and then the Reliability and Validity coefficients were extracted. The results showed the following: One, the adaptation the educational curricula to pupils with visually handicapped has a natural level compared to the average satisfactory. Two, the adaptation of educational programs to pupils with visual handicapped has a natural level compared to the average satisfactory. The researcher presented a set of recommendations and suggestions: First, the Ministry of Education should establish a guide booklet to be a guide or reference for any institute or school that includes special classes in order to know the effective ways in the process of adapting the curricula and educational programs for students with visual disabilities.